The smuggling linked to informal merchandise trade in the argentine northwest and its relationship with economic development - Cid Ferreira, Lucia (Universidad Nacional del Litoral, 2019)
The paper was carried out within the framework of an investigation that seeks to answer the following questions: How is economic development related to the criminal issue in Argentina? Have the economic «models» adopted in recent decades exerted a differentiated influence on the evolution of crime? How? A first advance has exposed a set of observations on the evolution of crime registered in Argentina in relation to the economic contexts of the last twenty-five years. The present intends to move forward on a specific delictual universe and relatively different from that of conventional or common crimes: that of «economic crimes». These are those that, while being able to affect individual patrimony, are characterized by affecting the economic organization that governs a society. On this occasion, we address the crime of smuggling linked to the informal merchandise trade, with regard to the conflicts that occurred in northwestern Argentina in 2017. The current impossibility of having an adequate empirical basis to deal with this type of crime is recognized, which is why we try to find out, through secondary sources, the record of their social dynamics and the qualitative and quantitative data that would be. Between the conclusions it is indicated that more important than the possible influence of the models, are the effects of the economic laws of the development of the capitalism in the local and global frame.